A transitions perspective on coastal sustainability - Morrissey, John; Heidkamp, C. Patrick (Towards coastal resilience and sustainability, 2018)
This chapter presents a review of the multi-scalar complexities of coastal sustainability challenges. It focuses on three discrete vignettes of innovation, which range from a novel and emerging innovation, a maturing innovation and an innovation which has become mainstream and part of the prevailing socio-technical regime. The first vignette focuses on 3D ocean farming off the coast of Connecticut in Long Island Sound, USA, as an example of an emerging niche-level innovation. The second vignette discusses the development of offshore wind energy capacity in Liverpool Bay, UK as an example of a socio-technical innovation that is more mature. The final vignette discusses containerisation as an example of a fully matured socio-technological change. The chapter argues that a spatial perspective on transition is critical to adequately account for uneven development processes and to recognise the heterogeneity of different places in terms of potential for low-carbon transition. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Barium alloys; Coastal sustainability; Development process; Liverpool bays; Low-carbon transitions; Off-shore wind energy; Offshore oil well production; Socio-technical regimes; Sociotechnical; Sustainable development; Technological change; Wind power; dept.egm